Urinary calprotectin, NGAL, and KIM-1 in the differentiation of primarily inflammatory vs. non-inflammatory stable chronic kidney diseases. Issue 1 (1st January 2021) - Seibert, Felix S.; Sitz, Maximilian; Passfall, Jürgen; Haesner, Martin; Laschinski, Peter; Buhl, Martin; Bauer, Frederic; Rohn, Benjamin; Babel, Nina; Westhoff, Timm H.
Abstract: Introduction: It has been demonstrated that urinary neutrophil gelatinase-associated lipocalin (NGAL) and calprotectin are helpful biomarkers in the differentiation of intrinsic and prerenal acute kidney injury. Objective: The present cross-sectional study investigates, whether urinary biomarkers are able to differentiate primarily inflammatory from non-inflammatory entities in chronic kidney disease (CKD). Methods: Urinary calprotectin, NGAL, and kidney injury molecule-1 (KIM-1) concentrations were assessed in a study population of 143 patients with stable CKD and 29 healthy controls. Stable renal function was defined as an eGFR fluctuation ≤5 ml/min/1.73 m 2 in the past 12 months. Pyuria, metastatic carcinoma, and renal transplantation were regarded as exclusion criteria. Diabetic nephropathy, hypertensive nephropathy, and polycystic kidney disease were categorized as 'primarily non-inflammatory renal diseases' (NIRD), whereas glomerulonephritis and vasculitis were regarded as 'primarily inflammatory renal diseases' (IRD). Results: Urinary calprotectin and NGAL concentrations significantly differed between CKD and healthy controls ( p < 0.05 each), whereas KIM-1 concentrations did not ( p = 0.84). The three biomarkers did neither show significant differences in-between the individual entities, nor the two categories of IRD vs. NIRD (calprotectin 155.7 vs. 96.99 ng/ml; NGAL 14 896 vs. 11 977 pg/ml; KIM-1 1388 vs. 1009 pg/ml; p > 0.05 each). Albumin exceeds the diagnostic power of the investigated biomarkers by far. Conclusions: The urinary biomarkers calprotectin, NGAL, and KIM-1 have no diagnostic value in the differentiation of primarily inflammatory vs. non-inflammatory etiologies of CKD.